2014
DOI: 10.3390/ijms150713060
|View full text |Cite
|
Sign up to set email alerts
|

Possible Prognostic and Therapeutic Significance of c-Kit Expression, Mast Cell Count and Microvessel Density in Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) is the most frequent renal tumor and its incidence is increasing worldwide. Tumor angiogenesis is known to play a crucial role in the etiopathogenesis of RCC and over the last few years an even deeper knowledge of its contribution in metastatic RCC development has led to the development of numerous molecular targeting agents (such as sunitinib, sorafenib, pazopanib, axitinib, tivozanib, and dovitinib). The above agents are principally directed against vascular endothelial growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 71 publications
1
33
1
Order By: Relevance
“…VEGF and its receptor VEGFR2 were extensively tested primary therapeutic targets currently in clinical for renal cell carcinoma (RCC), and the development of RCC was proved to be relied on VEGF signaling and its receptor [42]. Similar to VEGFR2, c-Kit was proposed essential in the occurrence and development of the metastatic RCC, and its overexpression was well demonstrated in the chromophobe variety of RCC [43]. Thus, VEGFR2 and c-Kit were identified as the most popular therapeutic targets of approved multi-target drugs, and the binding of which could provide substantial influence on the pathogenesis of the RCC.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF and its receptor VEGFR2 were extensively tested primary therapeutic targets currently in clinical for renal cell carcinoma (RCC), and the development of RCC was proved to be relied on VEGF signaling and its receptor [42]. Similar to VEGFR2, c-Kit was proposed essential in the occurrence and development of the metastatic RCC, and its overexpression was well demonstrated in the chromophobe variety of RCC [43]. Thus, VEGFR2 and c-Kit were identified as the most popular therapeutic targets of approved multi-target drugs, and the binding of which could provide substantial influence on the pathogenesis of the RCC.…”
Section: Resultsmentioning
confidence: 99%
“…(22) Several studies have shown a correlation between clinical outcome and SCF, and mutations in the substrate binding pocket of SCF have been implicated in conferring resistance to TKIs. (23, 24) Less is known about the mechanistic role of the remaining two biomarkers, SAP and SHBG, in the pathogenesis of RCC, although some studies have suggested a prognostic role of SAP in the disease. (25) In an exploratory analysis, the four biomarkers noted herein were assessed in combination to generate a potential signature for response.…”
Section: Discussionmentioning
confidence: 99%
“…PDGFR signaling is also a promising target for RCC (23). Activation of the c-Kit receptor has been known to induce transduction signaling, including induction of the mitogen-activated protein kinase and phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathways in RCC, which in turn leads to mast cell activation (24).…”
Section: Discussionmentioning
confidence: 99%